Family and friends - Watkins, Howard K. (1977)
Albert Watkins, Dottie Pin, Stephanie Pin, Irene Williamson, Joyce Breiman, Christine Watkins; back: Cliff Williamson, Rose Watkins in front of Howard Arms Apartments